Visualization of Internal Carotid Artery Atherosclerotic Plaques in Symptomatic and Asymptomatic Patients: A Comparison of Optical Coherence Tomography and Intravascular Ultrasound - Yoshimura, S.; Kawasaki, M.; Yamada, K.; Enomoto, Y.; Egashira, Y.; Hattori, A.; Nishigaki, K.; Minatoguchi, S.; Iwama, T. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: OCT has been reported as a high-resolution imaging tool for characterizing plaque in the coronary arteries. The present study aimed to evaluate the ability of OCT to visualize carotid artery plaques compared with that of IVUS in asymptomatic and symptomatic patients. MATERIALS AND METHODS: OCT was performed for 34 plaques (17 symptomatic, 17 asymptomatic) in 30 patients during CAS under a proximal cerebral protection method. OCT was performed before balloon angioplasty and after stent placement. IVUS was also performed just after OCT. RESULTS: No technical or neurologic complications were encountered by using OCT. An inner catheter was used in 12 of 34 procedures (35.3%) for advancing the OCT image wire beyond the site of stenosis. OCT clearly visualized intraluminal thrombus in 15 of 34 plaques (44.1%), whereas IVUS detected a thrombus in 1 plaque (2.9%, P < .001). Neovascularization was demonstrated in 13 of 34 plaques (38.2%) by OCT, but not by IVUS (0%, P < .001). Intraluminal thrombus was more frequently observed in symptomatic plaques (13 of 17, 76.5%) than in asymptomatic plaques (2 of 17, 11.8%; P < .001). Interobserver and intraobserver variability with OCT diagnosis was excellent for thrombus, ulceration, neovascularization, and lipid pool. CONCLUSIONS: The present findings suggest that OCT can safely and precisely visualize human carotid plaques during CAS and that intraluminal thrombus and neovascularization are more frequently detected in symptomatic plaques. CAScarotid artery stentingHDLhigh-density lipoproteinIVUSintravascular ultrasoundLDLlow-density lipoproteinOCToptical coherence tomographySAPPHIREStenting and Angioplasty with Protection in Patients at High Risk for EndarterectomyVHvirtual histology-intravascular